Exploring the Impact of Emerging New Media and Communication Technologies on Society: A Scoping Review - Eko Putra Boediman (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2023)
This scoping review explores the impact of emerging new media and communication technologies on society, focusing on the effects of technologies on communication, culture, and social interaction. The study aims to provide an overview of recent research, analyze the potential benefits and drawbacks of new technologies such as social media, mobile devices, and other digital platforms. The study employs a scoping review methodology, which involves a systematic search and analysis of existing literature on the topic. The study examines some aspects of new media and communication technologies, including their impact on interpersonal communication, political discourse, and social movements. The findings suggest that new media and communication technologies have significant implications for society, shaping the way people interact and engage in public discourse. While these technologies have created new opportunities for communication and collaboration, they have also presented new challenges, such as the spread of misinformation and the erosion of privacy. This scoping review contributes to a deeper understanding of the impact of emerging technologies on society, highlighting the need for ongoing research and the development of policies and practices that promote responsible use and mitigate potential harms. The findings are important for scholars, practitioners and policymakers.